2022
DOI: 10.1111/nup.12401
|View full text |Cite
|
Sign up to set email alerts
|

What does person‐centred care mean, if you weren't considered a person anyway: An engagement with person‐centred care and Black, queer, feminist, and posthuman approaches

Abstract: Despite the prominence of person-centred care (PCC) in nursing, there is no general agreement on the assumptions and the meaning of PCC. We sympathize with the work of others who rethink PCC towards relational, embedded, and temporal selfhood rather than individual personhood. Our perspective addresses criticism of humanist assumptions in PCC using critical posthumanism as a diffraction from dominant values We highlight the problematic realities that might be produced in healthcare, leading to some people bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 95 publications
0
18
0
1
Order By: Relevance
“…In this paper, I have shown that nursing benefits from a philosophical posthumanist scholarship focused on political agendas, for example, Dillard‐Wright (2022) and Smith et al (2022). As has been correctly pointed out by an anonymous reviewer of this manuscript, much of alternative philosophy generated by women and people of colour had little chance of entering the volumes of Western philosophy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this paper, I have shown that nursing benefits from a philosophical posthumanist scholarship focused on political agendas, for example, Dillard‐Wright (2022) and Smith et al (2022). As has been correctly pointed out by an anonymous reviewer of this manuscript, much of alternative philosophy generated by women and people of colour had little chance of entering the volumes of Western philosophy.…”
Section: Discussionmentioning
confidence: 99%
“…However, if one was never admitted into the category of ‘human’, can posthumanism still be of use? Smith et al (2022) ask this question and respond with an affirmation.…”
Section: The Western Humanistic Tradition From Cicero To Kantmentioning
confidence: 99%
See 1 more Smart Citation
“…Our panel concluded with the third presentation called ‘From Transhumanism to a Critical Posthumanism: An Ontological Dehierarchization of Living and Being’, which made an artful case for resistance, radical democracy, and dehierarchization in nursing for the benefit of nurses and the folks for whom they care. Content from the three interrelated presentations can be further explored in published papers that grounded the interrelated panel presentations (Martin & Laurin, 2023; Smith, Willis, Hopkins‐Walsh, 2022; Smith, Willis, Hopkins‐Walsh, Dillard‐Wright et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Leplege et al, 2007) and an idealizing and stereotyped view of the person. Equally, however, it may also reproduce stereotypes (Foth & Leibing, 2022; Imafidon, 2022; Smith et al, 2022; Tieu et al, 2022). Thus, person‐centredness must be related to the circumstances and conditions of our time and can be seen as a centrally ethical positioning for the shaping of healthcare practice and promotion of health.…”
Section: Introductionmentioning
confidence: 99%